FACTORS INFLUENCING AIS CAPABILITY AND PERFORMANCE OF MALAYSIAN CO-OPERATIVES: A CONCEPTUAL FRAMEWORK - Mohd Hadzrami Harun Rasit; Mohammad Azhar Ibrahim (International Journal of Accounting, Finance and Business, 2018)
Accounting information systems (AIS) capability is important because it involvesthe ability of AIS to process business data into useful information according to userrequirements. Indeed, empirical evidences suggested that the use of AIS has positive impacton firm performance. However, factors that contribute to building AIS capability which inturn improve firm performance were not adequately explained. As such, this paper draws onthe resource-based view (RBV) to define various dimensions of information systems (IS)resources. Previous studies were concentrating on small and medium-sized enterprises(SMEs) and public listed companies leaving a gap in co-operatives literatures. Also, priorstudies were focusing on specific AIS capability namely enterprise resources planning (ERP)and dynamic AIS capability using dynamic capabilities framework which is dissimilar fromthe current study. This paper contributes to the literature by providing a better understandingof the roles of IS resources in capability-building of AIS. This paper also contributes inestablishing the AIS capability-building framework within co-operatives environment inMalaysia.